A STUDY ON THE DIFFICULTIES IN BUILDING INTERROGATIVE SENTENCES FACED BY THE FIRST YEAR STUDENTS OF SMP MUHAMMADIYAH 5 SURAKARTA - RAHAYU , ARUM PUTRI (2007)
English in Indonesia is the first foreign language. In learning English the Students get a problem related to Indonesian and English. This condition happens to the first grade students of SMP Muhammadiyah 5 Surakarta. Common errors occur in their written productions. Therefore, the aim of this research is to describe the errors made by the students in conducting good interrogative sentences. The writer takes 37 students as the subject of the research. In this research, the writer uses elicitation method in collecting data. She asks the students to answer the tasks containing of 30 question three types of interrogative sentences. Based on the result of the data analysis, the writer finds 4 types of errors namely: 1) omission, 2) addition: a) double marking, b) simple addition, 3) misordering,and 4) mismatching. They are found in three types of interrogative sentences, namely: in yes-no questions (13, 69%), in wh-word questions (13, 60%), in tag questions (10, 72%). The dominant type of errors found is yes-no questions. There are four types of sources of errors namely: 1) interlingual transfer, 2) intralingual transfer, 3) the language system, and 4) context of learning. The result of this study is that most of the students still make errors in expressing their idea because of the influence of their first language structures.